Electrochemical performance of multifuel based nanocomposite for Solid Oxide Fuel Cell. Issue 7 (May 2020) - Shaheen, Kausar; Suo, Hongli; Shah, Zarbad; Hanif, Muhammad Bilal; Hussain, Zahid; Ali, Sajid; Liu, Min; Ma, Lin; Cui, Jin; Ji, Yao Tang; Wang, Yi
Abstract: The efficient performance of Solid Oxide Fuel Cell (SOFC) by utilizing safe and cost effective hydrocarbon fuels at low temperature is really a challenging task due to C –H activation and sluggish oxidation/reduction kinetics. In this study a novel [Sr0.4 La0.6 (Fe0.75 Ti0.25 )0.6 Ni0.4 O3-δ ] (SLFTNO) nanocomposite was synthesized via solid state reaction route and was evaluated electrochemically in presence of multifuels such as hydrogen, ammonia, methane and ethanol. Phase purity and structural analysis was carried out through X-Ray Diffractometer (XRD), X-ray Photoelectron Spectroscopy (XPS), Scanning Electron Microscope (SEM) and Transmission Electron Microscope (TEM). The average crystallite size calculated was ranged from 60-100 nm. The electrical conductivity and power density was measured between (89–226) S/cm and (147–318) mW/cm 2 respectively among different fuels. This study indicated the synthesized SLFTNO nanocomposite as stable and efficient multifuels candidate for SOFCs. Graphical abstract: Image 1